PENGARUH SOLVABILITAS DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PADA PERUSAHAAN LOGAM DAN SEJENISNYA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammad Salman; Nurlinda Sari; Nurismanidar (Jurnal Penelitian Ekonomi Akuntansi, 2019)
The purpose of this research is to analyze the effect of solvency and sales growth on profitability of metal companies and the like listed on the Indonesia Stock Exchange in the period 2010-2017. Solvency is proxied by Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) while profitability is proxied by Return On Asset (ROA). The sample in this study were companies that were obtained from population data of metal companies and the like that were listed on the Indonesia Stock Exchange (IDX). Data analysis methods used are the classic assumption test, multiple linear regression and hypothesis testing using SPSS 23 as an analysis tool. The results showed that Debt to Asset Ratio (DAR) had a positive and significant effect on Return On Assets (ROA), Debt to Equity Ratio (DER) had a negative and significant effect on Return on Assets (ROA) and sales growth did not significantly influence the Return On Asset (ROA). Based on simultaneous testing shows that the variable Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER) and sales growth has a significant effect on Return on Assets (ROA).